"A-π-A" type naphthalimide-based cathode interlayers for efficient organic solar cells. (January 2023) - Liu, Hao; Liu, Shaonan; Zhao, Yong; Jiang, Jilei; Feng, Xiaoran; Sun, Mingliang; Yu, Liangmin; Dai, Shuixing
Abstract: In this work, we designed and synthesized two "A-π-A" structural small molecules based on N -dimethylaminopropyl-1, 8-naphthalimide with π-bridge, namely 4, 4'-(thiophene-2, 5-diyl)bis(2-(3-(dimethylamino)propyl)-1H-benzo[de]isoquinoline-1, 3(2H)-dione) (ONTN) and 4, 4'-(1, 4-phenylene)bis(2-(3-(dimethylamino)propyl)-1H-benzo[de]isoquinoline-1, 3(2H)-dione) (ONBN), which are used as cathode interfacial materials (CIMs) to systematically reveal the effect of π-bridge of 1, 8-naphthalimide-based cathode interlayers for efficient organic solar cells (OSCs). Compared with ONBN, ONTN shows higher decomposition temperature, more red-shift absorption, lower LUMO and higher HOMO energy levels, higher electron mobility and conductivity, and more uniform film morphology. Both molecules exhibit excellent thermal stability and high light transmittance. The OSCs based on ONTN with PBDB-T:ITIC as active layer demonstrate a power conversion efficiency (PCE) of 10.38%, higher than the control device of ONBN (a PCE of 9.04%). It turns out that thiophene π-bridge 1, 8-naphthalimide-based ONTN got better performance as CIMs than that of ONBN with benzene π-bridge. Graphical abstract: Image 1 Highlights: We synthesize new building block 2-bromo-2-(3-(dimethylamino) propyl)-1H-benzo[de]isoquinoline-1, 3(2H)-dione and demonstrate its great potential for constructing cathode interfacial materials using in OSCs. We find that thiophene π-bridge in ONTN significantly enhances the device efficiency. We investigate effects of the π-bridge on electronic properties, charge transport, film morphology, and photovoltaic properties.